2014
DOI: 10.1159/000369254
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications from a Single-Center Study of Colorectal Adenocarcinoma in Transplant Recipients

Abstract: Background: With the increasing burden of organ transplant recipients and improvements in allograft outcome, the incidence of neoplasms rising from these patients is an important issue. Objective: In this study, we investigated transplant recipients with colorectal cancer to determine its incidence, clinicopathological characteristics, and prognosis. Methods: The database of Severance Hospital was queried for all cases of colorectal adenocarcinoma among transplant recipients from August 2005 to January 2013. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The increased risk of CRC after kidney transplantation has been well documented. [ 10 12 ] Moreover, compared with the general population, CRC that are diagnosed in kidney transplant patients often display a more aggressive behavior, and the aggressive behavior is characterized by an earlier age of cancer diagnosis, [ 13 ] a more advanced cancer stage (American joint committee on cancer stage > II), [ 14 ] and a lower 5-year survival. [ 13 , 15 ] Interestingly, a significantly reduced risk of rectal cancer was observed in the transplant recipients when separated from colon cancer, [ 16 , 17 ] and it seems that the elevated risk of CRC was driven by excess of proximal colon cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increased risk of CRC after kidney transplantation has been well documented. [ 10 12 ] Moreover, compared with the general population, CRC that are diagnosed in kidney transplant patients often display a more aggressive behavior, and the aggressive behavior is characterized by an earlier age of cancer diagnosis, [ 13 ] a more advanced cancer stage (American joint committee on cancer stage > II), [ 14 ] and a lower 5-year survival. [ 13 , 15 ] Interestingly, a significantly reduced risk of rectal cancer was observed in the transplant recipients when separated from colon cancer, [ 16 , 17 ] and it seems that the elevated risk of CRC was driven by excess of proximal colon cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found surgeries exerted a positive effect on survival of transplant patients with CRC. [ 14 , 19 ] Theoretically, these patients were supposed to be more susceptible to perioperative complications. However, Krysa [ 20 ] assessed the outcome of 21 kidney transplant recipients undergoing elective colorectal surgery, and suggested the results were favorable, with no transplant rejection, low morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%